2019
DOI: 10.1021/acschemneuro.9b00338
|View full text |Cite
|
Sign up to set email alerts
|

Novel HDAC6 Inhibitors Increase Tubulin Acetylation and Rescue Axonal Transport of Mitochondria in a Model of Charcot–Marie–Tooth Type 2F

Abstract: Disruption of axonal transport causes a number of rare, inherited axonopathies and is heavily implicated in a wide range of more common neurodegenerative disorders, many of them agerelated. Acetylation of α-tubulin is one important regulatory mechanism, influencing microtubule stability and motor protein attachment. Of several strategies so far used to enhance axonal transport, increasing microtubule acetylation through inhibition of the deacetylase enzyme HDAC6 has been one of the most effective. Several inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…The therapeutic potential of HDAC6 inhibition has been well established in CMT2F caused by the defective axonal transport. HDAC6 inhibition has been reported to enhance axonal transport and, thus, improve neuronal function (Adalbert et al, 2020; Benoy et al, 2017, 2018; d'Ydewalle et al, 2011; Mo et al, 2018). However, the therapeutic potential of HDAC6 inhibition has not yet been tested in CMT1A caused by the defective myelination of Schwann cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic potential of HDAC6 inhibition has been well established in CMT2F caused by the defective axonal transport. HDAC6 inhibition has been reported to enhance axonal transport and, thus, improve neuronal function (Adalbert et al, 2020; Benoy et al, 2017, 2018; d'Ydewalle et al, 2011; Mo et al, 2018). However, the therapeutic potential of HDAC6 inhibition has not yet been tested in CMT1A caused by the defective myelination of Schwann cells.…”
Section: Resultsmentioning
confidence: 99%
“…HDAC6 inhibition has been reported to enhance axonal transport and, thus, improve neuronal function (Adalbert et al, 2020;Benoy et al, 2017Benoy et al, , 2018d'Ydewalle et al, 2011;Mo et al, 2018). (Figure 2b,c).…”
Section: Ckd-504 Is a New Inhibitor Of Hdac6 Developed By The Chongmentioning
confidence: 98%
See 1 more Smart Citation
“…Dysregulated HDAC6 interactions with mutated MFN2 could lead to mitochondrial deficits that, based on the literature, may be one of many important factors in the development of CMT2A peripheral neuropathy (Baloh et al, 2007;Misko et al, 2010;Picci et al, 2020). Adalbert et al (2020) observed in a mouse model of CMT2F slowed and stunted movement of mitochondria, which was restored after inhibition of HDAC6 (D' Ydewalle et al, 2011). CMT2F is a subtype of CMT2 that is autosomal dominant and involves the heat shock protein family B (HSPB1) gene (Fridman et al, 2015;Bird, 2020).…”
Section: Mitochondrial Transport Is Altered In Models Of Peripheral Neuropathymentioning
confidence: 99%
“…Remarkably, in 2011 d'Ydewalle and colleagues discovered that the use of a selective HDAC6 inhibitor successfully reversed the clinical phenotype in HSPB1 S135F rodent models. 36 Further preclinical studies of these compounds in other models of axonal CMT have revealed promising results, 39,40 thereby paving the way for future clinical trials in patients.…”
Section: Discussionmentioning
confidence: 99%